A study of factors that influence the hand phone purchase among teenagers in Kota Bharu (case study of secondary school) / Fatin Nabila Mazlan - Mazlan, Fatin Nabila (2014)
The purpose of this research was to identify the most important factor that influences the hand phone purchase among teenagers in Kota Bharu. This research explored the contribute factors that influence the hand phone purchase among teenagers that includes the price, technology, and brand. The researcher used convenience sampling, where 150 questionnaires were distributed to the students of secondary schools such as Sekolah Menengah Zainab 1 and Sultan Ismail College in Kota Bharu. The researcher measured three independent variables which is the price, technology, and brand. The dependent variable that been use in this study was factor of hand phone purchase. The finding shows that all three independent variables have a relationship with factors of hand phone purchase. The method used by the researcher to get these result is by using the regression analysis. Therefore, all the variables contribute to the factor of hand phone purchase